Information Technology and Its Impact on Modern Classroom Dynamics: A Computer Science Perspective - Kusnadi, Kusnadi; Hatta, Muhammad; Brotosaputro, Goenawan; Amri, Amri; Harris, Sebastian (Pandawan, 2025)
The integration of Information Technology (IT) has significantly transformed modern education, particularly classroom dynamics, by enhancing accessibility to information and enabling personalized learning experiences. This paper aims to explore both the positive impacts and challenges of IT adoption in the classroom, focusing on the importance of Computer Science in shaping effective teaching practices. The study analyzes tools like Learning Management Systems (LMS), simulation software, and data analysis platforms, which improve engagement between students and teachers but also highlight challenges such as the digital divide and less interactive learning. Understanding fundamental Computer Science concepts, including algorithms, programming, and networking, is key to developing innovative solutions that enhance classroom learning. The results show that while IT has revolutionized education by facilitating online learning and collaboration, it also presents challenges that must be addressed, such as access to resources and the need for more interactive learning experiences. To optimize IT’s impact, the paper recommends continuous teacher training, better integration of technology with curricula, and improved access to devices and internet connectivity, ensuring a more inclusive and innovative learning environment in the digital age.